Glucocorticoids enhance acid activation of the Na(+)/H(+) exchanger 3 (NHE3) - Ambühl, Patrice M. (American Society for Clinical Investigation, 1999)
In the absence of exogenous glucocorticoids, decreasing media pH (from 7.4 to 6.8) for 24 hours increased the Na(+)/H(+) exchanger 3 (NHE3) activity in opossum kidney (OKP) cells. 10(–7) M and 10(–8) M hydrocortisone increased NHE3 activity, and in their presence, acid incubation further increased NHE3 activity. Hydrocortisone (10(–9) M) had no effect on NHE3 activity, but in its presence, the effect of acid incubation on NHE3 activity increased twofold. Aldosterone (10(–8) M) had no effect. In the absence of hydrocortisone, acid incubation increased NHE3 protein abundance by 47%; in the presence of 10(–9) M hydrocortisone, acid incubation increased NHE3 protein abundance by 132%. The increase in NHE3 protein abundance was dependent on protein synthesis. However, 10(–9) M hydrocortisone did not modify the effect of acid incubation to cause a twofold increase in NHE3 mRNA abundance. In the absence of protein synthesis, 10(–9) M hydrocortisone did potentiate an effect of acid on NHE3 activity, which was due to trafficking of NHE3 to the apical membrane. These results suggest that glucocorticoids and acid interact synergistically at the level of NHE3 translation and trafficking.